Binasal Endoscopic Approach to the Sellar Region: Experience and Outcome Analysis of 80 Cases - El-Fiki, Mohamed E.; Aly, Ahmed; Elwany, Samy (Journal of Neurological Surgery Part B: Skull Base, 2012)
A prospective study was performed on 80 cases of different types of sellar lesions during the period between January 2007 and December 2010. The binasal approach was used in all patients. Functioning lesions were diagnosed in 59 patients. The most common secretory tumors were prolactinomas (37 patients) followed by adrenocorticotropic hormone producing tumors (11 patients) and growth hormone producing tumors (11 patients). Nonfunctioning lesions included: 14 pituitary adenomas, 2 chordomas, 2 metastatic lesions (ovarian carcinoma and thyroid carcinoma), and 1 case of sarcoidosis, Rathke's cleft cyst, and craniopharyngioma. Seven nonfunctioning cases developed apoplexy. Among the 59 patients with functioning pituitary lesions, postoperative endocrinological control was achieved in 51 of them (86.5%) 3 months postoperatively with normalization of pituitary functions and complete tumor resection as proved by postoperative magnetic resonance imaging. Postoperative visual field defect improvement was achieved in 15 out of 23 patients (65.2%), including the cases with apoplexy, with complete tumor resection. Postoperative discomfort such as headache, vomiting, or dizziness was minimal and hospitalization period was 2 to 3 days. Postoperative leak continued in one patient in whom revision surgical repair was performed 7 days later. The merits, outcome, and limitations of the approach were discussed.
Keywords: pituitary; sella; binasal; endoscopic approach